A Novelty Method Subjectif of Electrical Power Cable Retirement Policy - Amani Darma Tarigan (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
An age data of the same type cables under the same operation condition in a regional transmission system was collected. Use a probability analysis method and the age data to calculate the reliability functions of normal distribution and Weibull distribution, which reflect the reliability level of cables. Effect Analysis system Failed mode (EAFM) is applied to find the characteristic fault parameters, which contribute to the cable failure and can be obtained by the preventive tests. Fuzzy membership function is constructed to estimate the failure probability. Fuzzy analytic hierarchy process (AHP) is employed to define the importance weight of failure mode, and the reliability value of the cable will be gained through the weighted average method. It is estimated by using the reliability function and the cable reliability value that the expected damage cost (EDC) of the transmission system is caused by cable failure. The interest income can be gained by delaying the retirement of the aging cable. Finally, an appropriate time of the cable retirement is found when making an economic comparison between the EDA and the interest income due to the retirement delay.